Analyzing the Impact of the Automation Train Protection Implementation in Indonesia - Pangaribuan, Grace; Malkhamah, Siti; Muthohar, Imam (ASTONJADRO, 2024)
Indonesian railway industry has grown dramatically in the past five years, with network and track length expected to triple by 2030. This is due to increasing railway demand. The Indonesian National Rail Network has averaged 350 million passengers per year for the past decade. The 2015 high was 450 million, and the 2020 low was 200 million. The Republic of Indonesia improves its infrastructure, especially trains. MRT Jakarta, LRT Jakarta-Bogor-Depok-Bekasi, Jakarta-Bandung high-speed rail, and conventional long-distance train in Sumatera, Makassar to Pare-Pare in Sulawesi Island are among the recent railway projects in Indonesia. In contrast, Indonesian rail safety systems fail to meet rail demand. There is no proper rail safety system exists for the national mainline network. The Indonesian mainline railway uses the Grade of Automation 0, with the train driver as the main controller. This country has several railway accidents, which frequent to cause fatality. Indonesian rail accidents include collisions, derailments, train slips, and natural disasters. Indonesia had 15.62 train-km fatalities per thousand-kilometre railway in 2017. The US had 725.4 railway fatalities per billion km in 2000–2009, whereas the EU had 353.1 in 2006–2009. It is obvious that the rate of train accident in Indonesia is higher compared to other countries. Accordingly, the improvement of rail safety is essential in order to support national mobility. One promising direction to reduce this fatality is through the Automatic Train Protection System. This technology has kind of like several benefits, such as controlling and maintaining the train speed during operation. The most basic version of this system is able to provide audible and visual warnings to train drivers when they approach certain signals. If the driver does not respond to these warnings and the train continues to move in dangerously, the automatic train protection can automatically apply the brakes to stop the train. Installing automatic train protection system is expected to reduce the number of accidents caused by human error and improve the overall performance of the rail network. This study finds that there is significant reduction in the number of rail accidents by implementing the Train Automatic Protection in Indonesian Railways. The benefit is not only reducing the number of accident cost but also the non-monetised aspects.